PORTRAIT OF ECONOMIC POTENTIAL IN BADUNG REGENCY, BALI - Soeharjoto Soekapdjo; Debbie Aryani Tribudhi; Dini Hariyanti; Lucky Nugroho; Roikhan Machamad Aziz (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Successful of regional development is inseparable from region ability in exploring and developing its economic potential. Economic potential is dynamic according to the conditions. Aims of this study is to find out Badung regency economic potential in 2011-2018. Data comes from Central Bureau of Statistics of Bali province and Badung regency, using location quotient, Dynamic Location Quotient, Klassen Typology and Shift Share method. Result of this analysis is Badung regency has economic potential to be developed into a locomotive of regional development in the real estate sector that has become the base sector, superior, and due to its location, then followed by the agricultural, forestry, and fishery sectors that have become the base sector, developing, and due to its location. This sector needs to be supported by synergistic policies in order to provide multiplier effect in other sectors.